Genome-Wide Association Analysis of Incident Coronary Heart Disease (CHD) in African Americans: A Short Report - Barbalic, Maja; Reiner, Alex P.; Wu, Chunyuan; Hixson, James E.; Franceschini, Nora; Eaton, Charles B.; Heiss, Gerardo; Couper, David; Mosley, Thomas; Boerwinkle, Eric (PLoS genetics, 2011)
African Americans have the highest rate of mortality due to coronary heart disease (CHD). Although multiple loci have been identified influencing CHD risk in European-Americans using a genome-wide association (GWAS) approach, no GWAS of incident CHD has been reported for African Americans. We performed a GWAS for incident CHD events collected during 19 years of follow-up in 2,905 African Americans from the Atherosclerosis Risk in Communities (ARIC) study. We identified a genome-wide significant SNP (rs1859023, MAF = 31%) located at 7q21 near the PFTK1 gene (HR = 0.57, 95% CI 0.46 to 0.69, p = 1.86×10(-08)), which replicated in an independent sample of over 8,000 African American women from the Women's Health Initiative (WHI) (HR = 0.81, 95% CI 0.70 to 0.93, p = 0.005). PFTK1 encodes a serine/threonine-protein kinase, PFTAIRE-1, that acts as a cyclin-dependent kinase regulating cell cycle progression and cell proliferation. This is the first finding of incident CHD locus identified by GWAS in African Americans.